Chapter Shaping Gods: from Göbekli Tepe to Kaneš, Ḫattuša, and Beyond - Alfonso, Archi (Studia Asiana, 2023)
The spectacular finds at Göbekli Tepe and Nevali Çorı: monolithic pillars representing stylized humans decorated with a large variety of animals, are the representation of an animist cosmos, in which animals and plants being may appear as persons, capable of will. Çatal Höyük represents a stage in which gods started to be shaped: the bull represented the Storm-god (a concept which reached the Classical period), the stag the god of the wild fauna, and female figurines symbolized the Mother-goddess. In Egypt, where gods where usually represented by animals, zoomorphism presents a continuity which ended only with the introduction of Christianity. The archaeological finds from Kaneš and the Hittite texts document an extraordinary continuity: each deity was represented by an animal, portraited in the vessel with which the celebrant (the royal couple or also a priest) reached a kind of communion with the god in drinking of the same wine and eating of the same bread.